The routledge handbook of positive communication : contributions of an emerging community of research on communication for happiness and social change - Muñiz Velázquez, José Antonio; Pulido, Cristina M. (New York [etc.] Routledge, 2019)
The Routledge Handbook of Positive Communication forms a comprehensive reference point for cross-disciplinary approaches to understanding the central role of communication in the construction of hedonic and eudemonic happiness,or subjective and psychological well-being. Including contributions from internationally recognized authors in their respective fields, this reference uses as its focus five main scenarios where communication affects the life of individuals: mass and digital media, advertising and marketing communication, external and internal communication in companies and organizations, communication in education, and communication in daily life interactions.
Keywords: Comunicación; Medios de comunicación social